Human-Nature Bond: A Study on Shakespeare’s Selected Sonnets - Paudel , Bhagabat (Academia Research Journal, 2025)
Shakespeare’s sonnets are free from monolithic knowledge credited to God. The paper critically acknowledges the complex relationship between humans and nature since ages particularly in Shakespeare’s selected sonnets, highlighting ecological values in the context of real-world challenges such as deforestation, pollution, and resource exploitation. Within the framework of his sonnet, the paper focuses on ecology and its impact on contemporary Europe. The paper draws on the views of writers spanning from Romanticism to the latest perspectives on ecocriticism and climate justice. It observes through the lens of ecocritical readings of Shakespeare. The sonnets are solid proofs of ecological consciousness. The paper wraps up on how human actions have a direct impact on environmental stability, highlighting the interconnectedness of social, economic, and ecological systems. He draws a metaphor from Nature to demonstrate that Nature is superior to human beings. At the same time, he expresses his most profound love to his beloved.